Dengue - should we look for confirmation? - Srigade, Vedavyasa; Bingi, Koteshwar (Indian Journal of Child Health, 2016)
Background: Children are at great risk of dengue infection and mortality. Pediatric dengue management needs early identification and timely intervention. Objective: Evidence for case management based on clinical diagnosis without waiting for confirmation is aimed at in this study. Methods: Retrospective medical record review of pediatric clinical and confirmed dengue cases was done. Children admitted during 6 months in 2015 at Institute of Child Health, Niloufer Hospital, Hyderabad, were included in the study. 3 demographic, 32 symptom, 24 sign, and 24 investigation data were collected. Proportions of individual findings of the total number of patients in the group were compared between clinical and confirmed dengue groups. Results: Of the 13,750 admissions, 282 serologically confirmed dengue cases, 407 clinical dengue cases, 4 confirmed dengue deaths, and 24 clinical dengue deaths, making a total of 717 patient data were analyzed. Case fatality rate was 4.06% (95% confidence interval: 2.56-5.57). Except 9 out of 83 parameters, no significant differences of proportions between the groups were present. Age <5 years, seizures, altered sensorium, bradycardia, and systolic blood pressure <70 mmHg were significantly associated with increased mortality in dengue on logistic regression. Conclusions: Clinical diagnosis in the light of epidemiology, using acute pain in right hypochondrium, malena, tender hepatomegaly, centrifugal blanchable flushing, and hypotension as definite pointers of dengue avoids vagueness and is sufficient to treat dengue with escalation of fluid therapy as needed and with other supportive measures without waiting for lab support. Currently, available investigations cannot confirm dengue with accuracy in the hour of need, but they should be used for epidemiological purposes.